Optimalisasi Digital Marketing dan Meminimalisir Ketimpangan Pada Peternak di Desa Sumberdem - Rivo, Rivo Abramovich Manurung; Josephine Chevania Daeli; Nadhifa Azka; Jihan Maharani Dewi; Naufal Syafiq Aqil; Astrida Fitri Nuryani (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Digitalization has become a crucial element in various sectors, including livestock farming. This article explores the optimization of digital marketing to enhance economic potential and minimize social disparities among farmers in Sumberdem Village, Wonosari District, Malang Regency. The majority of the village's residents work as livestock farmers, particularly goat farmers. However, there is a gap between younger farmers who have adopted modern technologies and others who have not. Through outreach programs and videography competitions, farmers were educated on business management, animal health, and digital marketing strategies. This approach aims to empower farmers to utilize technology for expanding market networks, improving productivity, and reducing economic disparities. The results of this program indicate increased digital skills among the community, the creation of more attractive livestock business branding, and more inclusive economic opportunities. By optimizing sustainable natural resources, this program is expected to comprehensively support the welfare of the Sumberdem Village community.